Analisis Manajemen Organisasi dan Sumber Daya Manusia (Studi Kasus pada Industri Velg Mobil) - Tatbita Titin Suhariyanto; Raden Achmad Chairdino Leuveano; Suhariyanto Suhariyanto (OPSI, 2020)
Due to the importance of organizational management and human resources (HR) in the company, this study intends to analyze several aspects related to these two things, such as internal and external conditions of the company, existing business strategies, existing organizational structures, and job descriptions in a position. This research chooses one of the long-standing car alloy wheels industry. By conducting SWOT method, observations and interviews, there are some conclusions about the company's existing conditions and the formulation of new business strategies. The recommendations proposed in this study include to optimize opportunities and to strengthen the internal factors of the company (SO strategy), to design a new organizational structure with the addition of several specific positions, and to design HR strategies to be more competent.